PROCESS OF A SCHIZOPHRENIC’S DIALOGUES IN A BEAUTIFUL MIND MOVIE - Siska Pratiwi; Rahmah Rahmah (State University of Medan, 2013)
ABSTRACT This study is concerned to transitivity system, focusing in the types of process which were uttered by the schizophrenic in A Beautiful Mind movie, John Nash. This study was conducted by using descriptive qualitative method. There were six types of process in transitivity system. The results of data analysis showed the total numbers were: material process 44.67%, mental process 18.83%, relational process 28.03%, behavioral process 1.17%, verbal process 4.53% and existential process 2.77%. The most dominant process is material process, that is the process which indicates action; activities and events, things happen and people or other actors do things or make them happen. It occurred because many statements showed Nash’s activities with real people and hallucination people especially when Nash’s hallucination friends about Charles, Parcher and Marcee were kept in his mind and he talked much with them about their activities because he met his hallucination friends intensively. Keywords: schizophrenia, transitivity, process, movie